Percutaneous Nephrostomy Tube-related Infections. (4th October 2017) - El Haddad, Hanine; Viola, George; Jiang, Ying; Raad, Issam; Rolston, Kenneth V; Szvalb, Ariel
Abstract: Background: Percutaneous nephrostomy tubes (PCN) are indicated for relief of urinary tract obstruction. These devices are prone to mechanical and infectious complications. The infection rate at 90 days is ±20%. Our objective was to determine whether discordant antimicrobial coverage provided prior to PCN exchange was associated with a higher rate of recurrent infection compared with those who received concordant therapy. Methods: We retrospectively reviewed 780 patients that had undergone initial PCN placement at our institution between July 2014 and February 2017. We only included patients that had developed a definite PCN infection, subsequent PCN exchange, with a minimum 30 day post-PCN exchange follow up. We defined PCN infection as the presence of a positive urine culture (≥10 4 cfu/mL) plus symptoms consistent with a urinary tract infection. Recurrence was defined as a new PCN infection with the isolation of the same organism to the initial episode. Antibiotics were defined as concordant if they had activity against all organisms' isolated based on antimicrobial susceptibilities. Results: A total of 47 patients met our inclusion criteria. The median age of patients was 59, with 49% being male. The most common underlying tumors were urothelial (45%), cervical (17%) and prostate cancer (15%). Clinical characteristics included ureteral stents (17%), diabetes (19%), history of GU surgery (38%), and active chemotherapy at the time of PCN insertion (70%). The median time to onset of infection was 42 days. Infections were polymicrobial in 50% of the cases. The most common organisms encountered were Pseudomonas spp. (36%), Enterococcus spp. (23%) and Escherichia coli (18%). The median length of follow up of PCN tubes after exchange was 55 days. There were 12 (26%) recurrences occurring at a median time of 27 days. The provision of discordant antibiotics preceding PCN exchange was significantly associated with recurrence of infection (66.7% vs. 12.8%; P < 0.002). Conclusion: Discordant antimicrobial therapy provided during PCN exchange, in the setting of a PCN infection is associated with a higher rate of relapse. Therefore, to decrease the high rate for PCN reinfection, we propose that prior to PCN exchange secondary to infection, patients should be receiving concordant antimicrobial therapy. Disclosures: All authors: No reported disclosures.